Perancangan Aplikasi Permainan “Kemuliaan dan Kehormatan : Perang Legenda” Sebagai Media Promosi Kebudayaan Daerah di indonesia - Yenna Sopia Situmorang; Bangkit Rizki Aqsad Mananda; Fauzi, Amir Hasanudin (Journal of Applied Engineering and Social Science (JAESS), 2025)
This project develops a PC-based game to promote cultural diversity in the digital era. The abstract summarizes the game's concept, design, gameplay, and impact on cultural awareness and intercultural interactions. The game celebrates diverse cultural heritage through engaging, immersive gameplay. Characters and environments are inspired by various cultures, with graphics and designs reflecting their visual elements. Gameplay mechanics consider cultural aspects, featuring specialized combat techniques. The sound and music enhance the cultural experience, providing an engaging audiovisual experience. Beyond entertainment, the game educates players about different cultures, raising awareness of global cultural diversity and encouraging appreciation. The PC-based game "War of Legends: Glory and Honor" has significant potential to enhance understanding and appreciation of Indonesian cultures.